(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1999)
In the Piobbico area (Pesaro, Central Italy, Inner Marchean Basin), outcrops of Paleogene to Early Miocene pelagic sediments are widespread and mainly consist of marls and marly limestones. In this paper two sections have been considered in the near Pieve d’Accinelli (PDA and PDA bis). A detailed biostratigraphic study was performed on planktonic foraminiferal assemblages using the standard zonations. PDA bis section spans from Early Oligocene to basal Aquitanian (Zone P20 to Subzone N4a), while PDA section is included in Zone N4 (Early Aquitanian). "Standard" bioevents such as the LO (Last Occurrence) of "Globigerina" ampliapertura, Chiloguembelina spp., Paragloborotalia opima opima and the FO (First Occurrence) of Paragloborotalia kugleri and of Globoquadrina dehiscens, together with other "added" bioevents, have been identified. Moreover, several peaks in abundance occur such as a fair peak of Dentoglobigerina in the middle-upper portion of Subzone P21b, a strong increase in abundance of Tenuitella and Catapsydrax groups in Subzone P21b, an increase in abundance of Dentoglobigerina at the top of Zone P22, of Globoquadrina in Subzone N4a, of Globigerinoides spp. at the top of Subzone N4a and of Globoquadrina dehiscens in Subzone N4b. A preliminary study of dinoflagellate cyst assemblages was carried out around Early Oligocene/Late Oligocene boundary. Two bioevents such as a peak in abundance of Svalbardella cooksonae at the base of Subzone P21b and the FO of Impaginodinium minor at the base of Zone P22 have been identified. On the ground of a semiquantitative analysis of the planktonic foraminiferal assemblages, a paleoclimatic pattern has been tentatively inferred. This analysis suggests cool-temperate conditions at the top of Zone P20. In the lower part of the Late Oligocene the assemblages indicate the outset of very cool conditions, while the interval that spans Zone P22 to Subzone N4b is characterized by a generalized paleoclimatic instability.